2012
DOI: 10.1016/j.talanta.2012.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Detection of trace levels of lead in aqueous liquids using extractive electrospray ionization tandem mass spectrometry

Abstract: a b s t r a c tA sensitive approach, based on semi-quantitative measurement of the characteristic fragments in multistage extractive electrospray ionization mass spectrometry (EESI-MS n ), was developed for fast detection of trace levels of lead in aqueous liquids including mineral water, lake water, tap water, energy drinks, soft drinks, beer, orange juice, and tea. A disodium ethylene-diamine-tetraacetic acid (EDTA) aqueous solution was electrosprayed to produce negatively charged primary ions which then int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…the fragment at m/z 143 of [ 63 Cu(NO 3 )∙2H 2 O] + for copper and m/z 162 of [ 98 MoO 3 (NO 3 )] − for molybdenum, respectively. Some previous studies have shown that the quantitative performance of MS n is better than that of the primary MS because the MS 2 mass spectrum generally has better signal noise ratio. The plots of the measured MS 2 fragment intensities versus the concentrations showed a good linear relationship in water solutions with the linear correlation square coefficients 0.994 for copper and 0.965 for molybdenum, respectively, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the fragment at m/z 143 of [ 63 Cu(NO 3 )∙2H 2 O] + for copper and m/z 162 of [ 98 MoO 3 (NO 3 )] − for molybdenum, respectively. Some previous studies have shown that the quantitative performance of MS n is better than that of the primary MS because the MS 2 mass spectrum generally has better signal noise ratio. The plots of the measured MS 2 fragment intensities versus the concentrations showed a good linear relationship in water solutions with the linear correlation square coefficients 0.994 for copper and 0.965 for molybdenum, respectively, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the combination of separation (IC or CE) with ESI‐MS is an appropriate approach . In contrast to ICP‐MS, the ESI‐MS technique allows for simultaneous identification of unknown compounds in the sample or confirmation of the presence of known chemical moieties without appropriate standards, based on the obtained mass spectra . This is of great importance during speciation studies focused on metal cations which occur as metal‐organic ligand complexes.…”
Section: Resultsmentioning
confidence: 99%
“…1 as previously reported. 24,25 Herein, the angle ␣ between the spray outlet and the heated capillary of the LTQ instrument was maintained at about 150°, which was equivalent to the angle between sample beam and the heated capillary of the LTQ instrument. The angle ␤ between the sample plume outlet and the electrospray beam was about 60°.…”
Section: Methodsmentioning
confidence: 99%